Exercise training and low level laser therapy as a modulate to pain relief and functional changes in knee osteoarthritis - Kholvadia, Aayesha (My University, 2019)
Background Evidence shows that the global prevalence of knee osteoarthritis (KOA) is high, with limited data on the management of the disease. The use of novel modalities to treat the condition is low due to poor understanding of their clinical effects. Therefore there are gaps in the knowledge on the prevalence and treatment modalities for patients diagnosed with KOA. Aim: The aim was threefold; (i) to determine the prevalence of KOA in South Africa aged 45yrs-75yrs; (ii) to determine the current management of KOA; and (iii) to determine the effect of Low Level Laser therapy (LLLT) on the structural and functional components related to KOA in a South African cohort, aged 45-75yrs. Methods: The methodology will be discussed in terms of the three specified objectives; (i) prevalence study data - a self-reported data collection sheet listing 19 relevant ICD 10 codes; completed by South African medical aid providers. (ii) The treatment paradigm study, which encompassed a deemed KOA management paradigm validated questionnaire sent electronically to 742 general, specialist and allied practitioners, identifying the incidence of KOA and deemed efficacy and compliance of various management tool. These practitioners were identified from a database of medical and allied practitioners in both the private and public sector of South Africa. The questionnaire consisted of two close ended questions indicating the incidence of KOA and bilateral KOA patients consulted at the practice; one choice question indicating the most suggested mode of therapy from a choice of pharmaceutical, surgical, homeopathic, physical exercise therapy and LLLT and finally, 3 Likert type scale questions on the deemed efficacy and compliance of the modes of therapy as stated above. (iii) The intervention study which was a randomized controlled trial (RCT) utilizing pre marked questionnaire sheets on 111 participants. Participants were randomized into one of three intervention groups; (1) exercise group (n=39), (2) LLLT group (n=40), and (3) combined exercise-LLLT group (n=32). Data on knee circumference, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), knee range of motion (ROM) and the one minute timed sit–to-stand test was used. These tests were done at four time points: (T1) baseline, (T2) post-12 session intervention, (T3) one month post intervention and (T4) three months post intervention. Results: The results will be discussed in terms of the three specified objectives; (i) The prevalence of KOA was reported as 17.5%, 28.0% and 38.5% in a South African population over 45yrs. (ii) Four hundred and thirteen clinicians completed the questionnaire, reporting a KOA patient intake of 53%. Pharmacology (36.3%) and physical exercise (35.3%) was the most common management protocols compared to surgical intervention, homeopathy and LLLT. Pharmacotherapy (73%) and physical exercise (92%) were observed as effective treatments. Seventy five percent of all practitioners responded with an answer of “no comment” when asked the deemed efficacy of LLLT. Practitioners viewed patients with KOA to have low compliance with physical exercise and pharmacotherapy (iii) the participant demographic included 86 females and 25 males, the average age reported was 61.8 ± 5.6yrs. At 12-week follow-up, knee circumference decreased significantly in all groups (p<0.05), the effect was highest in the LLLT group. All groups experienced improvements in the WOMAC pain scale, but the LLLT group showed the greatest improvement (p<0.05). Knee ROM values improved significantly across all three groups; however, the effect of the intervention was most significant (p<0.005) in the combined LLLT-exercise group. Physical functionality scores showed a greater improvement in the combined LLLTexercise group at all three data collection points. Conclusions: The estimated prevalence of KOA is 17-35% based on data collected from a specified South African cohort. Pharmacotherapy is a commonly suggested KOA management mode, whilst clinicians view physical exercise as effective. LLLT was not a known tool for the treatment of KOA. In addition to the improved functionality observed, pain was lowered significantly, particularly in the combined exercise-LLLT group. Study results have shown that LLLT used in isolation or in combination with physical exercise is an effective management tool.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2019
Keywords: Osteoarthritis--Treatment; Lasers--therapeutic use; Knee joint--pathology.